Pancrelipase as Adjunctive Therapy in Severe SCOT Deficiency: A Case of a Novel OXCT1 Gene Deletion - Mo'ath Abu Hamdeh; Lema Jaber; Jamal Abdullah; Anas Manhal; Mahmoud M. Qouqas; Mohammed Aldwaik; Sarah Abu Rmeilah; Mutaz Sultan; Shaher Shweiki; Nadirah Damseh (JIMD Reports)
ABSTRACT Succinyl‐CoA: 3‐oxoacid CoA transferase (SCOT) deficiency is a rare autosomal recessive disorder caused by biallelic sequence variants in the OXCT1 gene. This deficiency disrupts ketone body utilization, resulting in ketone accumulation and ketoacidosis. Clinical manifestations typically include respiratory distress, vomiting, lethargy, and, in severe cases, coma. This case presents the first known instance of severe SCOT deficiency resulting from a novel homozygous four‐exon deletion (exons 4–7) in the OXCT1 gene. The proband presented at the age of 3 months with severe metabolic acidosis that was refractory to conventional management. Despite high doses of bicarbonate therapy and cornstarch, he remained dependent on intravenous glucose for weeks. Repeated attempts to discontinue intravenous glucose led to severe acidosis within 12–24 h. The introduction of pancreatic enzyme replacement therapy (Creon) significantly enhanced starch digestion and absorption, stabilizing his metabolic condition and enabling discharge within 3 days. This case highlights the therapeutic potential of combining pancreatic enzyme replacement with cornstarch in infants under 12 months of age, given their limited pancreatic amylase activity. It underscores a potential management strategy for infants with severe forms of inherited metabolic disorders, such as SCOT deficiency and glycogen storage disease type I, where cornstarch is a cornerstone of therapy.